Physico-chemical properties of CrMoN coatings-combined experimental and computational studies - N. Jaf, Zainab; Jiang, Zhong Tao; A. Miran, Hussein; Altarawneh, Mohammednoor; Jean, Pierre Veder; Minakshi, Manickam; Zhou, Zhi Feng; Lim, H. N.; Huang, N. M.; Dlugogorski, Bogdan Z. (Elsevier, 2020)
In this study, Cr−Mo−N thin films with different Mo contents were synthesised via closed field unbalanced magnetron sputtering ion plating. The effects of Mo content on the microstructure, chemical bonding state, and optical properties of the prepared films were investigated by X-ray diffraction spectroscopy (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy, and ultraviolet-visible spectrophotometry. XRD results determined the face centered cubic (fcc) structure of pure CrN film. The incorporation of molybdenum (Mo) in the CrN matrix was confirmed by both XRD and XPS analyses. The CrMoN coatings demonstrate various polycrystalline phases including CrN, γ-Mo2N, Cr with oxides layers of MoO3, CrO3, and Cr2O3. Microstructural results of the Cr-Mo-N coatings show that the grain size increased with an increase in Mo content due to the formation of MoN phase, in which the Mo atoms interact with N atoms around the grain boundaries of the CrN phase. XPS investigations confirmed the presence of Cr, Mo, N, C and O elements in the studied coatings. The optical results revealed that the synthesised coatings exhibit low reflection magnitudes in the visible region of the solar spectrum indicating good antireflection surfaces. Mo doped thin coatings improve the solar absorptance by ~76% in the wavelength range of 200–800 nm with a low thermal emittance of ~ 20% in the infrared range (up to 4000 nm). Furthermore, by applying density functional theory, the computational simulation provides similar trends as the experimental finding of absorption coefficient in the wavelength range.